Anticancer Activity Assay of Some Purification Compounds Extracted from Pleurotus Ostreatus - M. Aljubori, Suhad; M. Alrufae, Mohammed; N. Alkelabi, Hamid (International Journal of Psychosocial Rehabilitation, 2020)
The present study is designed to evaluate some compounds extracted from Pleurotus ostreatus and purified using analytical and preparative HPLC techniques, then tested the anticancer activity by in vitro crystal violet (C.V) cytotoxicity assay on cancer and normal cell lines; chemical descriptions of these compounds were done by GC-MS technique. Analytical and preparative HPLC carried out with a 25% methanol with 1% formic acid mobile phase and description of about 12 fractions with retention times (9, 10, 11.5, 12, 12.5, 13.5, 14.7, 15.5, 17, 18, 19.5-21,21.8) at 254 nm, respectively. In vitro C.V. cytotoxicity assay on SW-480 colon cancer cell line appeared to have excellent inhibition with (1, 5, 6, 7, 12) fractions with (1000, 500, 250, 125, 62.5 μg/ml), while the same fractions have no effect on the Vero-101 normal cell line. GC-MS analysis data gave us the most probable anticancer compounds in these fractions, such as quinoline, 1H indole, silane compounds, and N-hexadecanoic acid.